Vasculitis of the upper airways1 (Swiss Medical Weekly, 2012)
Systemic vasculitides are rare and potentially life-threatening diseases. Granulomatosis with polyangiitis (GPA; formerly Wegener’s granulomatosis) and Churg Strauss syndrome (possibly to be renamed eosinophilic granulomatosis with polyangiitis; EGPA) are the 2 chief systemic vasculitides which may involve the upper respiratory tract. Chronic allergic rhinitis and nasal polyposis in EGPA, and recurrent sinusitis and/or otitis in both conditions, are not specific and can thus represent real diagnostic challenges if they are the first manifestations of the disease. Nasal septum perforation, saddle nose deformity and/or subglottic stenosis (SGS), although not totally specific, are more suggestive of GPA. Because upper airway manifestations often tend to be refractory to systemic therapy and/or to linger, local treatment represents a major aspect of management of the condition, especially for patients with SGS.